(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Even though more and more dyslexic students can be found in higher education, their situation is still poorly researched and known in Hungary; there are only few publications on this topic. During their studies, they often face obstacles that hinder their social integration and their ability to completely become European citizens. Their second language acquisition particularly proves to be challenging. In many cases, their completion in higher education, the obtainment of their degree and the launch of their real "adult" and "working" life are depended on a language exam. In this study, I present my research carried out among dyslexic students in Hungarian higher education by highlighting the experiences and difficulties related to their foreign language learning. I sincerely hope that in this way I can contribute to a better understanding and improvement of the situation of those affected.